Effective marketing : creating and keeping customers - Zikmund, William G.; D'Amico, Michael (Cincinnati, OH : South-Western College, 1998)
This book is about: Analysis of market and consumer behavior; Product strategy; Distribution strategy; Intergrated marketing communications; Pricing strategy.
Keywords: Marketing; Management; Marketing; Consumer behavior; Export marketing